The Relationship Of Preeclampsy With Premature Events : Literature Review - Dwi Astari Suja'nah; Nasrudin Andi Mappaware; Ajardiana Idrus; Abadi Aman; Trika Irianta; Fery Wijaya (Sean Institute, 2024)
Increased blood pressure during pregnancy up to ≥140/90 accompanied by proteinuria or Other organ failure is called preeclampsia. Preeclampsia is a manifestation of hypertension in pregnancy which occurs in 2–8% of pregnancies worldwide . Premature birth is defined as birth before 37 weeks of gestation (20-37 weeks) or with a fetal weight of less than 2500 grams. Objective from review literature This is to determine the relationship between preeclampsia and the incidence of prematurity . Using the literature review method with the PRISMA Flow Diagram principles. Article or journal scientific downloaded from PubMed , Portals Garuda, And Google Scholar with standard SYNTA IV and V. Key words in the search for this article are preeclampsia, birth, prematurity . Got it 1 5 0 articles in search results. All articles were selected based on the inclusion criteria obtained 20 research articles that will be reviewed. The results of the study show that there is a relationship between pre-eclampsia and the incidence of preterm labor.